2022
DOI: 10.1002/sdtp.15656
|View full text |Cite
|
Sign up to set email alerts
|

72‐1: In‐Line Mura Detection using Convolutional Neural Network in Display Manufacturing

Abstract: This paper discusses the automatic detection of mura, which has been a long‐standing challenge in the display industries. Using a dataset of 8000 images of OLED (Organic Light Emitting Diode) displays including four different types of mura, we found that a CNN (Convolutional Neural Network) having four or five sets of convolution and max‐pooling layers can detect mura with the accuracy more than 0.8. To improve detection of low contrast mura, we employed a contrast‐enhancement method and a subspace‐method, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In a recent study [ 52 ], authors utilized Convolutional Neural Networks (CNNs) for the detection of mura defects. The proposed research was evaluated on OLED images and identified four types of mura defects.…”
Section: Experiments and Results Analysismentioning
confidence: 99%
“…In a recent study [ 52 ], authors utilized Convolutional Neural Networks (CNNs) for the detection of mura defects. The proposed research was evaluated on OLED images and identified four types of mura defects.…”
Section: Experiments and Results Analysismentioning
confidence: 99%
“…1a). Pixel defects and line defects with specific shapes are already automatically detected through image processing, and M ura defects, which require complex analysis and algorithms due to uncertain edge shapes, are being detected through improved technology [1][2][3][4][5]. In particular, machine learning and deep learning are being used as core keys for such research.…”
Section: Introductionmentioning
confidence: 99%